Ranyard’s “Bible women” and their Programme of saving the poor - Olga Yablonskaya (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article is devoted to the activities of E. Renyard and her organization «London Bible and Domestic Female Mission». The reasons for the appearance of the mission, the features and directions of activity, the importance in solving the problems of pauperism are analyzed. It is emphasized that the movement was not so much ecclesiastical as socio-economic in nature. The author notes the special role of E. Renyard. She formulated the goals, objectives, principles of the organization. Renyard shared the idea that saving the inhabitants of the slums from poverty and degradation is possible without revolutionary reorganization of society, but through the personal efforts of the poor. The conditions for improvement were familiarization with Christianity, teaching a rational vision of the economy, and moral education. To create a favorable environment for the transformation of the inhabitants of the slums, «Bible women» distributed the texts of the Holy Scriptures among them, improved their lives by teaching women how to cook, clean, needlework, economical housekeeping, selling household items on installments. The article points out that women were the main object of activity of biblical scholars because of their social vulnerability and the decisive role in maintaining family foundations and raising children. Renyard hired for the purposes of the mission believing representatives of the working classes, who knew from their own experience the needs of residents of disadvantaged areas. Work in the mission provided them with a salary, education, and contributed to an increase in social status. Particular attention is paid to the first «Bible woman» – Marian, who carried out a number of important programs to improve the lives of the poor. The organization of biblical women received the support of society, the practice spread throughout the country and the world. The author comes to the conclusion that thanks to the efforts of Renyard and her mission, thousands of paupers were able to improve their lives, get rid of vices, become respectable citizens of the country, and evangelization on other continents contributed to the spread of Christian values around the world.